Use of Kaolin in the Pharmaceutical and Cosmetic Industries - Nurul Fadhilah (Pt. Anagata Sembagi Education, 2024)
Kaolin, a white clay mineral composed mainly of kaolinite with the chemical formula Al2O3.2SiO2.2H2O, has been a subject of interest since the days of medieval western literature. This interest increased especially after the advent of a more empirical approach to pharmacology, the establishment of pharmacopoeias, and developments in mineralogy, chemistry, as well as pharmaceutical technology. The use of kaolin in pharmaceutical (both topical and oral) and cosmetic applications has become important. Although it has long been recognized as a remedy in traditional medicine, the use of kaolin as an active ingredient for various diseases continues to be researched. Unfortunately, research focused on the use of kaolin in pharmaceuticals and cosmetics is still fairly limited. Therefore, this article aims to highlight the role and benefits of kaolin in both fields. Kaolin has been shown to have antibacterial, antiviral, and antidiarrheal properties when administered orally, as well as serve as a skin-protective agent when used topically. Aside from being an active ingredient, kaolin is also often used as an excipient in pharmaceutical formulations, acting as a filler, emulsifier, suspending agent, and crusher. In the cosmetic world, kaolin is often used as a sunscreen and to treat the skin. This article is organized based on a literature review of various articles and journals relevant to the topic discussed.